ҚУРЪОН МАЪНОЛАРИНИ ТАРЖИМА ВА ТАФСИР ҚИЛИШ УСТУВОР ВАЗИФА - Бауатдинов, Ш. (SCIENCE and SOCIETY, 2019)
The article contains information about the peculiarities of translation, from one language into another translation of the content of Koran and peculiarities of interpretation.